A new species of Neophyllachora (Phyllachoraceae, Phyllachorales) on Ficus altissima (Moraceae) in Southwestern China - Wang, Yi-Tong; Wu, Hai-Xia; Wijayawardene, Nalin N.; Song, Jia-Yu; Gong, Cui-Ling; Li, Zi-Yi (Phytotaxa, 2026)
Neophyllachora species are parasitic on the leaves of dicotyledonous plants. In this study, a new species of Neophyllachora, N. tongbiguanensis, was introduced from Yunnan Province, China, based on morpho-molecular analyses. A multi-gene phylogenetic analysis (based on large subunit rRNA, internal transcribed spacer region, and small subunit rRNA) was conducted using Maximum Likelihood (ML) and Bayesian Inference (BI) methods to clarify its taxonomic position. Our study provides a detailed description, illustrations, and a phylogenetic tree showing the position of this new species. The key to the species of Neophyllachora is also provided. These findings enrich the taxonomic diversity of Neophyllachora and provide valuable morphological and molecular data for its classification.